2012
DOI: 10.3109/10826084.2012.695419
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Serving Venues in South Africa as Sites of Risk and Potential Protection for Violence Against Women

Abstract: This qualitative study explores alcohol-serving venues as sites of risk or protection from violence against women (VAW) in one South African community. In 2010, we conducted in-depth interviews with 31 female patrons, 13 male patrons and 11 venue staff, and conducted structured observations in six alcohol venues. VAW was a common experience and venues contributed to risk through aggression, negative attitudes towards women, risks leaving the venues, and owners tolerating VAW. Concurrently, venues offered poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…This qualitative study was part of a larger mixed-methods study on alcohol use, gender and risk outcomes in alcohol-serving venues (Choi et al 2013; Sikkema et al 2011; Watt et al 2012) that was conducted in Delft, a township located on the outskirts of Cape Town, South Africa. Delft was established in 1990 by the government as a subsidized housing community for residents of both Black African (typically Xhosa-speaking) and Coloured (a South African ethnic group of mixed ancestry; typically Afrikaans-speaking) ethnicities.…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative study was part of a larger mixed-methods study on alcohol use, gender and risk outcomes in alcohol-serving venues (Choi et al 2013; Sikkema et al 2011; Watt et al 2012) that was conducted in Delft, a township located on the outskirts of Cape Town, South Africa. Delft was established in 1990 by the government as a subsidized housing community for residents of both Black African (typically Xhosa-speaking) and Coloured (a South African ethnic group of mixed ancestry; typically Afrikaans-speaking) ethnicities.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals who meet sex partners at venues have a higher risk of HIV acquisition than patrons who meet sex partners elsewhere (22). Venue attendance has been associated with increased risk of perpetrating or experiencing physical and sexual violence, greater number of sex partners, and higher rates of unprotected vaginal intercourse (13,23,24). …”
Section: Introductionmentioning
confidence: 99%
“…Although women are vulnerable to physical and sexual violence in alcohol-serving venues, some report feeling more empowered and safer in the venues than at home (24). Both men and women report visiting venues in order to bond with their peers and relax (18,25), and women may frequent the venues to escape stressors of their home lives (25-27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research has found that men and women frequent shebeens for social interactions, and women in particular regard the venues as places for them to bond with peers and escape home stressors (Choi et al, 2013; Watt, Aunon, Skinner, Sikkema, MacFarlane, et al, 2012). The venues also serve as social arenas for individuals to meet sexual partners (Weir, Morroni, Coetzee, Spencer, & Boerma, 2002) and our previous research has demonstrated that unprotected sex (Sikkema et al, 2011), transactional sex (including the exchange of sex for alcohol) (Watt, Aunon, Skinner, Sikkema, Kalichman, et al, 2012), and gender-based violence (Watt, Aunon, Skinner, Sikkema, MacFarlane, et al, 2012) frequently occur in these venues. These findings demonstrate both the importance of venues as social settings and the vulnerability of patrons to HIV acquisition.…”
Section: Introductionmentioning
confidence: 99%